The Clinical Features of Children With Acute Fulminant Myocarditis and the Diagnostic and Follow-Up Value of Cardiovascular Magnetic Resonance - Lv, Jianli; Han, Bo; Wang, Cuiyan; Wang, Jing; Jiang, Diandong; Zhao, Lijian; Yi, Yingchun; Zhang, Jianjun (Frontiers in Pediatrics, 2019)
Objective: To investigate the clinical features and the diagnostic and follow-up value of acute fulminant myocarditis (AFM) in children. Methods: A total of 20 children diagnosed with AFM admitted to our department were reviewed, and the clinical manifestations; pathogenic examination results; myocardial injury biomarkers; and electrocardiography, echocardiogram, and cardiovascular magnetic resonance (CMR) results were analyzed. Results: Twenty children with AFM, including 12 males and 8 females, aged 3–16 years, were analyzed. The initial symptoms were abdominal pain, vomiting, fatigue, syncope, and convulsions. All children had significantly increased hs-cTnT and NT-pro BNP. In addition to nonspecific ST-T changes, there were 10 cases of complete atrioventricular block, 2 cases of advanced atrioventricular block, and 1 case of ventricular tachycardia. Echocardiography showed an increase in the cardiac chamber sizes in 15 patients and a decrease in left ventricular ejection fraction (LVEF) in 17 patients. There were 16 patients with abnormal CMR findings, including 13 cases of high T2-weighted image (T2WI) signal and 14 cases of late gadolinium enhancement (LGE). In the patients who underwent CMR within 14 days of onset, the sensitivity of T2WI and LGE and the positive diagnosis rate were higher than in those who underwent CMR after 14 days, but the difference was not statistically significant. CMR was followed up in 10 patients: 7 patients returned to normal, 2 patients still had mild LGE, and 1 patient developed inflammatory dilated cardiomyopathy. All patients were treated with high-dose immunoglobulin, 11 of whom received high-dose immunoglobulin combined with glucocorticoids. Eight patients received temporary pacemakers, and 1 patient received ECMO. None of the patients died. The peak of hs-cTnT was significantly higher in the glucocorticoid group than in the unused glucocorticoid group (2853.4 ± 2217.2 and 1124.7 ± 527.3 pg/ml, respectively). Conclusion: Children with AFM have unique clinical features. Early identification and effective treatment can reduce the mortality rate and improve the prognosis. CMR is highly sensitive in the diagnosis of ARM, especially within 14 days of onset, and is a useful noninvasive imaging technique for the early identification of AFM in children. The dynamic observation and follow-up of children with AFM through CMR can guide clinical decision-making and prognosis assessment.